ANALISIS PERBEDAAN TINGKAT LIKUIDITAS BPR KONVENSIONAL DAN BPR SYARIAH GUNA MENGETAHUI TINGKAT KESEHATAN KEUANGAN BANK PERKREDITAN RAKYAT (STUDI PADA BPR DI KABUPATEN MAGETAN DAN PONOROGO) - Anggita Langgeng Wijaya; Yulin Suswandari (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2014)
This study is aimed to analyze the differences in the level of liquidity in Conventional Rural Banks and Islamic Rural Banks to determine the level of financial health of rurals banks in Magetan and Ponorogo East Java. Analyses were performed by t-test on liquidity ratio and cash ratio from periods 2010 until 2013. Population in this study are all of Rural banks (BPR) in Magetan and Ponorogo officially registered in Bank Indonesia. Data were obtained from the Quarterly financial report. The results of this research show that: 1) there are significant differences in terms of the liquidity ratio betweent Conventional Rural banks and Islamic Rural Bank at Magetan dan Ponorogo. Conventional Rural Banks have a higher liquidity ratio than Islamic Rural banks. 2) There aresignificant differences interms of the ratio of cash between conventional Rural Banks and Islamic Rural Bank in Magetan and Ponorogo. Conventional Rural Banks have a lower cash ratio than Islamic Rural Banks in Magetan and Ponorogo.